Peran Integrasi Logistik dalam Meningkatkan Pengaruh Praktik Manajemen Rantai Pasok terhadap Keunggulan Kompetitif - Lintang Stiaji; Titik Kusmantini (Jurnal Ilmu Manajemen, 2026)
This study aims to analyze the role of logistics integration in strengthening the influence of supply chain management practices on the competitive advantage of MSMEs producing frozen food in Bantul Regency. The study uses a quantitative approach with a survey method involving MSME actors as research respondents. Data collection was carried out through the distribution of structured questionnaires, while data analysis used the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The results show that Supply Chain Management (SCM) practices have a positive and significant influence on logistics integration and competitive advantage. Other findings show that logistics integration also has a positive effect on the competitive advantage of MSMEs. In addition, logistics integration has been proven to be able to mediate the relationship between SCM practices and competitive advantage, so that the implementation of an integrated supply chain can strengthen business competitiveness. The implementation of effective SCM practices encourages improvement in operational efficiency, distribution accuracy, product quality, and the ability of MSMEs to meet market needs in a sustainable manner. This research provides an empirical contribution on the importance of logistics integration in supporting the success of supply chain strategies, especially in the frozen food MSME sector which faces increasingly dynamic business competition. The research findings are expected to be a reference for MSME actors in developing a more effective distribution system and supply chain management to increase competitive advantage in a sustainable manner.